Conceptual and practical challenges associated with understanding patient safety within community‐based mental health services - Phoebe Averill; Charles Vincent; Gurpreet Reen; Claire Henderson; Nick Sevdalis (Wiley, 2023)
Abstract Introduction Patient safety problems stemming from healthcare delivery constitute a global public health concern and represent a pervasive barrier to improving care quality and clinical outcomes. However, evidence generation into safety in mental health care, particularly regarding community‐based mental health services, has long fallen behind that of physical health care, forming the focus of fewer research publications and developed largely in isolation from the wider improvement science discipline. We aimed to investigate the state of the field, along with key conceptual and empirical challenges to understanding patient safety in community‐based mental health care. Methods A narrative review surveyed the literature to appraise the conceptual obstacles to advancing the science of patient safety in community‐based mental health services. Sources were identified through a combination of a systematic search strategy and targeted searches of theoretical and empirical evidence from the fields of mental health care, patient safety and improvement science. Results Amongst available evidence, challenges in defining safety in the context of community mental health care, evaluating safety in long‐term care journeys and establishing what constitutes a 'preventable' safety problem, were identified. A dominant risk management approach to safety in mental health care, positioning service users as the origin of risk, has seemingly prevented a focus on proactive safety promotion, considering iatrogenic harm and latent system hazards. Conclusion We propose a wider conceptualization of safety and discuss the next steps for the integration and mobilization of disparate sources of 'safety intelligence', to advance how safety is conceived and addressed within community mental health care. Patient and Public Contribution This paper was part of a larger research project aimed at understanding and improving patient safety in community‐based mental health care. Although service users, carers and healthcare professionals were not involved as part of this narrative review, the views of these stakeholder groups were central to shaping the wider research project. For a qualitative interview and focus group study conducted alongside this review, interview topic guides were informed by this narrative analysis, designed jointly and piloted with a consultation group of service users and carers with experience of community‐based mental health services for working‐age adults, who advised on key questioning priorities.